IMPLEMENTASI PEMBELAJARAN DALAM JARINGAN PADA MATA PELAJARAN MATEMATIKA PADA PESERTA DIDIK DI SEKOLAH MENENGAH ATAS NEGERI 9 PALEMBANG - Amelia Amel Purnama (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2023)
This study aims to determine the process of online learning when it is implemented in SMA Negeri 9 Palembang and the impact of this implementation. The research method used in this study is a descriptive qualitative research method using data collection techniques, namely interview techniques. Researchers used interview techniques by collecting information obtained from informants at the school. From the data obtained by the researchers concluded that learning in the network, especially in mathematics is considered less effective. This is due to the lack of focus on students when the teacher gives explanations through the network because in fact mathematics lessons must be explained directly to students.